2019
DOI: 10.18393/ejss.560745
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of salinity in chickpea by Plant Growth Promoting Rhizobacteria and salicylic acid

Abstract: For growth or development of pulses, biotic and abiotic environmental factors are more conspicuous under stress conditions. For the survival against abiotic stresses, salicylic acid (SA) is reported a universal remedy. At the Soil Bacteriology Section, Ayub Agricultural Research Institute, Faisalabad, a pot study was conducted to monitor the role of Plant Growth Promoting Rhizobacteria (PGPR) and Salicylic acid in chickpea under salt stress. Eight treatments including control PGPR inoculation and Salicylic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…When applied exogenously, both PGPR and SA resulted in improved growth and increased biomass output in the presence of salt stress. Similar findings were reported by Aneela et al [40] and Khan et al [41], who observed increased growth even under salt-stress conditions after applying PGPR or SA.…”
Section: Discussionsupporting
confidence: 90%
“…When applied exogenously, both PGPR and SA resulted in improved growth and increased biomass output in the presence of salt stress. Similar findings were reported by Aneela et al [40] and Khan et al [41], who observed increased growth even under salt-stress conditions after applying PGPR or SA.…”
Section: Discussionsupporting
confidence: 90%
“…Given its role in both SAR and mitigation of abiotic stress, salicylic acid may be described as a defense hormone. In one study, the addition of salicylic acid, along with PGPB, to chickpea plants under high salt stress significantly increased the ameliorative response of the PGPB by itself [ 56 ]. In this and other studies, salicylic acid appeared to function synergistically with PGPB-encoded mechanisms [ 57 , 58 ].…”
Section: Salicylic Acidmentioning
confidence: 99%
“…Two PGPR strains P. aeruginosa and Burkholderia gladioli are reported in mitigating Cadmium toxicity in tomato seedlings by producing various phenolic compounds ( Khanna et al., 2019 ). Another study reported that supplementing salicylic acid with PGPRs can increase the yields significantly and alleviate salinity stress in chickpea ( Aneela et al., 2019 ). Bacillus velezensis provides resistance to wheat against various abiotic stresses viz.…”
Section: Abiotic Stress Resistancementioning
confidence: 99%